2009
DOI: 10.1002/sej.71
|View full text |Cite
|
Sign up to set email alerts
|

Dance with the one that brought you? Venture capital firms and the retention of founder‐CEOs

Abstract: We consider how a venture capital fi rm's perceived uncertainty in new and uncertain industry environments affects its decisions to retain founder-CEOs at companies they take public. We further consider how the human capital of the founder-CEO, the overall experience of the venture capital fi rm (VCF), and the VCF's specifi c experience with the new industry moderate the relationship between industry-based uncertainty and founder-CEO retention. We explore these issues in the context of 340 venture capital fi r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 86 publications
2
45
0
Order By: Relevance
“…This measure represents the log of the total number of investments made by a VC firm prior to the time of investment in the focal entrepreneurial venture. Alternatively, I used the log of a VC firm's age, in the spirit of Pollock et al (2009), but the results are qualitatively similar.…”
Section: Vc Experiencementioning
confidence: 65%
See 2 more Smart Citations
“…This measure represents the log of the total number of investments made by a VC firm prior to the time of investment in the focal entrepreneurial venture. Alternatively, I used the log of a VC firm's age, in the spirit of Pollock et al (2009), but the results are qualitatively similar.…”
Section: Vc Experiencementioning
confidence: 65%
“…That is, I do not know how much of the venture performance can be attributed to the fact that better VCs are adding more value to the venture that they are financing or to the fact that better VCs are able to select better ventures (or entrepreneurs) to begin with. This study uses a control variable that measured VC investors' experience, in accordance with prior studies (Gompers et al, 2010;Pollock et al, 2009), but the two effects (i.e., VC's selection and value-adding effect) are lumped together in this measure. Future research should focus on developing readily applicable measures that allow for capturing VC firms' value-adding ability and selection ability separately, which would provide significant contributions to entrepreneurship studies.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…There is evidence that retention may also be higher for the technical founders than for the general managers, though this has not been tested on a large sample of IPOs (Boeker and Karichalil, 2002). Pollock et al (2009) found that CEO-founders were more likely to be present at the IPO when there was greater business certainty in the particular sector. Put differently, when the sector was competitive and uncertain the founder was less likely to be CEO at the time of the IPO.…”
Section: Iposmentioning
confidence: 89%
“…Our motivation is choosing this signal also stems from the divided empirical evidence on the issue of founders’ influence on post‐IPO performance (Pollock et al ., ). For example, Certo et al .…”
Section: Theory and Hypothesesmentioning
confidence: 97%